(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Poor glycemic control is significantly associated with the development of macrovascular complications of diabetes. C-reactive protein (CRP) is considered as a sensitive and independent risk factor for cardiovascular events. The aim of this study was to compare elevated CRP among controlled, moderately controlled and uncontrolled diabetic subjects in a Bangladeshi population. CRP and glycosylated hemoglobin A1c (HbA1c) were measured in 226 confirmed diabetic subjects purposively and randomly. Elevation of CRP in the moderately controlled (relative risk 1.64, P<0.01) and uncontrolled diabetic subjects (relative risk 1.8, P<0.001) were significantly higher than controlled diabetic subjects. HbA1c was significantly associated with the likelihood of elevated CRP in the moderately controlled diabetic subjects (OR:2.87, 95% CI: 1.41 to 5.87, P<0.01) and in the uncontrolled diabetic subjects (OR:3.83, 95% CI: 1.94 to 7.58, P<0.001). This study revealed that the likelihood of elevated CRP is associated with the increase of HbA1c in diabetic subjects. DOI: http://dx.doi.org/10.3329/bjmb.v4i2.13771 Bangladesh J Med Biochem 2011; 4(2): 17-19